2020
DOI: 10.1007/s00204-020-02925-w
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of anticancer drugs in human placental tissue explants and trophoblast cell lines

Abstract: The application of anticancer drugs during pregnancy is associated with placenta-related adverse pregnancy outcomes. Therefore, it is important to study placental toxicity of anticancer drugs. The aim of this study was to compare effects on viability and steroidogenesis in placental tissue explants and trophoblast cell lines. Third trimester placental tissue explants were exposed for 72 h (culture day 4–7) to a concentration range of doxorubicin, paclitaxel, cisplatin, carboplatin, crizotinib, gefitinib, imati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…A recent in vitro study on human cell lines showed that paclitaxel moderately affects explant viability and reduces cell viability by 50% or more in trophoblast cell lines [ 99 ]. The same results were reported with docetaxel, with a maximum 30% decrease in cell viability [ 96 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent in vitro study on human cell lines showed that paclitaxel moderately affects explant viability and reduces cell viability by 50% or more in trophoblast cell lines [ 99 ]. The same results were reported with docetaxel, with a maximum 30% decrease in cell viability [ 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…An in vitro study on human placental tissue explants and trophoblast cell lines exposed to cisplatin or carboplatin concluded that both drugs affect cell and tissue viability at clinically relevant concentrations [ 99 ]. Hence, more data on placental transfer are required.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct chemotherapy-induced toxic effects caused placental underdevelopment, but other causes, such as malnutrition, stress and immune suppression could not be ruled out [ 70 ]. Another in vitro study examining placental tissue explants of 3rd trimester pregnancies, which were exposed to various cytotoxic drugs at therapeutic plasma concentrations (between 1 µM and 100 µM), such as doxorubicin, paclitaxel, cisplatin, carboplatin, crizotinib, gefitinib, imatinib or sunitinib and all cytotoxic drugs but paclitaxel led to reduced cell and tissue viability within 72 h of exposure [ 72 ]. In vivo animal studies showed impaired umbilical cord blood flow parameters and reduced placenta efficiency when mice were treated with doxorubicin during gestation [ 73 ].…”
Section: Obstetrical Management In Women With Cancer In Pregnancymentioning
confidence: 99%